Metacognitive Awareness and Mathematics Achievement Among Secondary-Level Students in Nepal - Dahal, Prem Prasad; Bohara, Bhuban Bahadur (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Mathematics achievement at the secondary school level is a critical determinant of students’ academic progression and future career opportunities. Although international studies have consistently highlighted metacognitive awareness as an important factor influencing mathematics learning, empirical evidence from the Nepalese context, particularly at the secondary level, remains limited. This study aimed to examine the relationship between metacognitive awareness and mathematics achievement among secondary-level students in Bhaktapur District, Nepal. A quantitative correlational design was employed, involving 450 students from Grades 9 to 12 enrolled in both public and private schools. Metacognitive awareness was measured using an adapted Metacognitive Awareness Inventory, while mathematics achievement was obtained from students’ most recent test scores. Data was analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The results revealed a moderate and statistically significant positive relationship between metacognitive awareness and mathematics achievement, with metacognitive awareness explaining a substantial proportion of variance in students’ mathematics performance. No statistically significant differences were observed across gender or school type. These findings confirm the importance of metacognitive awareness as a meaningful correlation and predictor of mathematics achievement in the Nepalese secondary school context. The study highlights the need for integrating metacognitive strategy instruction, including planning, monitoring, and reflective evaluation, into secondary mathematics classrooms to enhance academic achievement and support the development of self-regulated learning skills.